1989
DOI: 10.3347/kjp.1989.27.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reacting and specific antigenic components in cystic fluid from metacestodes of Echinococcus granulosus and Taenia solium

Abstract: Sera from confirmed patients of 5 hydatidosis, 67 neurocysticercosis and 89 other parasitic diseases were tested for specific antibody (IgG) levels by ELISA to cystic fluid antigens from metacestodes of Echinococcus granulosus (HF) and Taenia solium (CF). All hydatidosis sera reacted positively to both HF and CF while neurocysticercosis sera did in 49.3% to HF and 85.1% to CF. The frequencies of cross-reactions were lower in other parasitic diseases to both antigens. By SDS-PAGE, protein bands of 64, 35, 22 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These antigens are responsible for the cross-reactivity between the parasites. Kong et al (1989) identified seven immunodominant proteins (135,100,86,64,39,35, and 24 kDa) recognized in individuals infected with E. granulosus with WB using vesicle liquid from T. solium metacestodes. Similarly, five individuals infected by E. granulosus recognized the immunodominant proteins of 64-68, 39-42, and 24 kDa from the same reaction using SE from T. solium metacestodes and T. saginata metacestodes.…”
Section: Discussionmentioning
confidence: 99%
“…These antigens are responsible for the cross-reactivity between the parasites. Kong et al (1989) identified seven immunodominant proteins (135,100,86,64,39,35, and 24 kDa) recognized in individuals infected with E. granulosus with WB using vesicle liquid from T. solium metacestodes. Similarly, five individuals infected by E. granulosus recognized the immunodominant proteins of 64-68, 39-42, and 24 kDa from the same reaction using SE from T. solium metacestodes and T. saginata metacestodes.…”
Section: Discussionmentioning
confidence: 99%
“…3) Cyst fluid had less cross-reactivity with other parasites, especially Echinococcus spp., than intact cysts. 7,8,15,16 Several studies have demonstrated that the 10-26-kD antigen components of cysticerci are the ones most specific for differential serodiagnosis of NCC. 6,8,9 The GPs identified in our study appear to be equivalent to them.…”
Section: Discussionmentioning
confidence: 99%
“…Seven immunodominant proteins (135, 100, 86, 64, 39, 35 and 24kDa) had already been recognized in serum samples from individuals infected with Echinococcus granulosus, in IB using vesicle liquid from Taenia solium metacestodes 37 . In the present study, various proteins from saline antigen were also recognized in patients infected with Echinococcus granulosus, as demonstrated previously by our group 18 in relation to using Taenia saginata metacestodes.…”
Section: Discussionmentioning
confidence: 99%